Animals, Archetypes, and Advertising (A3): The Theory and the Practice of Customer Brand Symbolism - Lloyd, Stephen; Woodside, Arch (Routledge, 2013)
This study provides a theoretical grounding from social anthropology and psychoanalysis into the use of animal symbolism in marketing communications. The study analyses the adoption of animal symbols in brand communications, and considers these as either implicitly anthropomorphic (totemic) or explicitly anthropomorphic (fetishist). Contemporary advertising messages, as they become more visual, indirect, and implicit in their content (Phillips & McQuarrie, 2002), continue to employ animal symbols. Such integration of animal symbols serves to activate and connect archetypal associations automatically in consumers’ minds, thereby enabling them to activate the cultural schema that the brand represents. The effective application of cultural schema associated with a brand contributes to brand engagement and thereby to brand equity.